Management of Empty Pesticide Containers—A Study of Practices in Santa Cruz, Bolivia. (28th June 2017) - Huici, Omar; Skovgaard, Marlene; Condarco, Guido; Jørs, Erik; Jensen, Olaf Chresten
Aims: The mismanagement of empty containers of pesticides, posing a risk to the environment and the health of people, has motivated the promotion of international policies and guidelines to mitigate such problems. Despite these guidelines, attention to this problem is inadequate in Bolivia. The objective was to study the knowledge and practical management of the containers and to implement a responsible management plan for empty pesticide containers. Methods: This study implemented the project from 2014 to 2016 in 2 municipalities of the Department of Santa Cruz. Integral and participatory processes of information, education, and training were used. A questionnaire study among pesticide users was used to investigate knowledge and management of the empty pesticide containers. Results: The authorities and the population responded to the program by taking a critical and active approach to the problem, improving their responsible practices, and 5500 kg of empty containers were collected. The cross-sectional study showed that 93% of the empty containers were disposed of in vulnerable places; 62% of the population did not know what triple washing is; 60% felt discomfort, headache, and/or dizziness while using pesticides; and 31% of the empty containers had pesticide residue inside them. Conclusions: The study illustrates a complex situation, mainly caused by lack of knowledge and clear guidelines. We recommend documentation of the social, economic, and productive characteristics of the region before any municipal program action is undertaken. The key element to sustainable change is an informed and coordinated participation of all actors.